Pathological complete remission in ALK-positive lung cancer patient after multiple lines of conversion therapy - Que, Dan; Zou, Hongbo; Mao, Bijing; Zhang, Huan; Liang, Wei; Liu, Qin; Ke, Leiyu; Guo, Lijie; Xie, Qichao (Frontiers in Oncology, 2022)
Traditional therapeutic approaches for the treatment of advanced non-small-cell lung cancer (NSCLC) are based on chemotherapy. However, the discovery and understanding of oncogenic driver alterations led to the development of targeted therapies that have substantially improved patient outcomes. Still, to date there have been no reports of patients with advanced anaplastic lymphoma kinase (ALK)-positive lung cancer achieving pathological complete remission (pCR) after multiple lines of transformation therapy. In this case, a 55-year-old man was diagnosed with ALK-positive, stage IV lung adenocarcinoma using immunohistochemistry and next generation sequencing (NGS) tests. Crizotinib and two other ATP-competitive ALK inhibitors, ceritinib and alectinib, were used respectively as first-line, second-line, and third-line therapy. The patient received treatment with crizotinib and achieved partial response (PR), but 5 months later the efficacy was evaluated as progressive disease (PD). Ceritinib was used as the second-line treatment, but the disease progressed 6 months later. Alectinib was used as the third-line treatment, but the efficacy was evaluated as PD. From April 2019 to November 2019, the patient received 4 cycles of induction chemotherapy with pemetrexed/carboplatin/bevacizumab and then switched to pemetrexed/bevacizumab as the fourth-line treatment, and received the fifth line treatment, cetuximab/paclitaxel liposome/nedaplatin, for 1 cycle, but the disease still progressed. Then the patient received the sixth line of treatment, carisozumab/lorlatinib, for 9 antitumor cycles, resulting in PR. The patient underwent surgery followed by maintenance treatment with loratinib and achieved pathologic complete response (pCR). To our knowledge, this is the first documented case of pCR in a patient with ALK-positive advanced lung adenocarcinoma treated with multiple lines of therapy followed by surgical treatment. This case reveals the possible survival benefit of multiple lines of treatment in ALK-positive advanced lung adenocarcinoma, suggesting that this regimen may be a potential new treatment option for refractory patients with poor prognosis.